Prevalensi Akomodasi Insufisiensi pada Mahasiswa Fakultas Kedokteran dan Ilmu Kesehatan UKRIDA Angkatan 2023 - Gosali, Vincentio Owen; Farfar, Inggrid Osya; Silaen, Desi Hartati (Universitas Kristen Krida Wacana, 2025)
Accommodation insufficiency is an accommodation disorder characterized by a lower accommodation amplitude than the minimum limit of the Hofstetter formula. Symptoms of accommodation are impaired near vision, asthenopia (eye fatigue), blur, headache, and visual discomfort. This study aims to determine the prevalence of accommodation insufficiency in FKIK UKRIDA students class of 2023. This study used descriptive quantitative research method and cross sectional research design with 150 respondents. Each subject was only observed once at the same time using the RAF Rule as a measuring instrument. Data collection was carried out from September to November. The prevalence of accommodation insufficiency in FKIK UKRIDA Batch 2023 students amounted to 2 people (1.3%) in both eyes, 6 people (4%) in the left eye, and 2 people (1.3%) in the right eye. Accommodation disorders can be influenced by age and refraction. The prevalence of accommodation insufficiency in FKIK UKRIDA students of 2023 is 1.3%. The highest number who experienced accommodation insufficiency was in the left eye, which was 4%. It is recommended that people pay more attention to their eye health by conducting routine eye examinations every 6 months-1 year.